Opaque assets and rollover risk - Toni Ahnert; Benjamin F. Nelson (Bank of Canada, 2016)
We model the asset-opacity choice of an intermediary subject to rollover risk in wholesale funding markets. Greater opacity means investors form more dispersed beliefs about an intermediary's profitability. The endogenous benefit of opacity is lower fragility when profitability is expected to be high. However, the endogenous cost of opacity is a "partial run," whereby some investors receive bad private signals about profitability and run, even though the intermediary is solvent. We find that intermediaries choose to be transparent (opaque) when expected profitability is low (high). Intermediaries with lessvolatile profitability are also more likely to choose to be opaque.
Keywords: G01; G2; 330; Financial institutions; Financial stability